Use of Various 2D to 3D Techniques for Documenting and Unveiling the Information From European Medieval and Renaissance Tombstones and Native American Rock Art. - Palonka, Radosław; Zych, Bolesław; Śliwa, Jakub; Niemiec, Dariusz; Lewińska, Paulina (Archaeometry, 2026)
This paper examines and compares methods of digital recording and analysis of fragmentarily preserved reliefs from Gothic and Renaissance tombstones at the Cistercian abbey in Mogiła, a district within the city of Kraków, southern Poland. The aim is to provide accurate documentation and examination of these reliefs through the use of various high‐resolution digital photography and terrestrial laser scanning techniques, followed by analysis in dedicated software. Additionally, the paper compares the digital methods employed in Kraków‐Mogiła with other studies conducted by part of the team in southwestern Colorado, USA, focusing on the digitization of Native American rock art from different time periods, primarily Ancestral Pueblo and historic Ute petroglyphs. Although these two areas and cultural traditions are distinct, they share a common focus on carved and engraved stones and rock surfaces. Our studies provided an opportunity to explore and refine methods and techniques for more effective digital recording and visualization of various types of relief carvings found in stone monuments. The objective was to capture, enhance, and visualize even the faintest and least preserved details of steles, tombstones, and rock art that would otherwise be challenging or impossible to document using traditional methods alone. In addition to the digital analysis and visualizations, extensive historical research was conducted during the study in Kraków‐Mogiła. This comprehensive approach led to unexpected discoveries, such as the identification of the missing tombstone of one of the most notable individuals buried in the Mogiła abbey.